The conscious universe : part and whole in modern physical theory - Kafatos, Minas C.; Nadeau, Robert, 1944- (New York : Springer-Verlag, 1990)
The authors show that a generalized principle of complementarity is pervasive not only in physical theories such as cosmological models of the universe but also in the constructions of all human realities. They suggest that consciousness can no longer be divorced from the problem of the way science operates. The book concludes by making the case that this realization entails a new way of understanding the universe that could obviate much of the current conflict between science and religion, while providing at the same time a basis for valuation that is better suited for coordinating all human experience. - Back cover.
Leaving the realm of the visualizable: waves, quanta, and the rise of quantum theory -- The strange new world of the quantum -- Bell's Theorem and the aspect experiments: coming to terms with quantum non-local reality -- Changing the rules: the new epistemology of science -- Searching for the ground: mutation, mind, and the epistemology of science -- Science and the quest for a new metaphysics -- The road untraveled: enlarging the new logical framework of complementarity -- The emergence of a new vision: the unfolding universe -- The ceremony of innocent: science and ethics.
Includes bibliographical references (p. 201-209) and index.
Keywords: Science -- Philosophy; Physics -- Philosophy; Quantum theory; Science -- Philosophy